Partiti politici e cittadinanza attiva: strategie di inclusione e culture partecipative nei programmi elettorali a Roma - Putini, Antonio (Studi Politici, 2022)
The article aims to give a representation of the strategic vision concerning participation and inclusion expressed by political parties’ electoral programs during the administrative polls held in the municipality of Rome in 2021. Which frames characterize the way parties look at civic engagement and social inclusion? Which are the tools with which parties deal with participation? Which function and which role should citizens play in the local governance system according to the vision of the main political parties? By using a quali-quantitative analysis of the election manifestos the article answers to these questions and depicts the political cultures beyond the electoral programs.